Experimental determination of the H2S mass transfer coefficient across the liquid–gas interface in gravity sewers. (8th July 2022) - Pacheco Fernández, Micaela; Barjenbruch, Matthias
Abstract: Hydrogen sulphide (H2 S) emissions in sewer systems lead to several problems such as corrosion, odour nuisances, and health damage to sewer workers. Although the gas is formed in the liquid phase, its effects are noticeable when released into the sewer atmosphere. Until recently, the lack of analytical procedures for continuous monitoring of H2 S in the liquid phase, as well as its toxicity, have challenged the quantification of the mass transfer coefficient under real conditions. Because of this, most studies have mainly focused on batch experiments with artificial wastewater and/or oxygen. The aim of this study was to experimentally determine the overall mass transfer coefficient for H2 S during intermittent pumping events common in actual sewer systems, using the two-film theory approach and employing online sensors for liquid and gas phase measurements. The mass transfer coefficient was quantified by carrying out 21 experiments with actual wastewater in a 25 m long gravity pipe of a sewer pilot plant located in Berlin (Germany). Results show that the corrected mass transfer coefficient (KL a20 ) during a pumping event ranged between 0.1 and 8 h −1 with a median value of 4.2 h −1, within the range of the results obtained by the most common empirical models. HIGHLIGHTS: Online sensors enable data acquisition for determining the H2 S mass transfer coefficients across the liquid–gas interface. Experiments were carried out in a sewer pilot plant with actual wastewater. During pumping the KL a20 coefficient for H2 S had a median value of 4.2 h −1 . Graphical Abstract